2022
DOI: 10.3389/fbioe.2022.973301
|View full text |Cite
|
Sign up to set email alerts
|

The application of collagen in the repair of peripheral nerve defect

Abstract: Collagen is a natural polymer expressed in the extracellular matrix of the peripheral nervous system. It has become increasingly crucial in peripheral nerve reconstruction as it was involved in regulating Schwann cell behaviors, maintaining peripheral nerve functions during peripheral nerve development, and being strongly upregulated after nerve injury to promote peripheral nerve regeneration. Moreover, its biological properties, such as low immunogenicity, excellent biocompatibility, and biodegradability make… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 216 publications
0
18
0
Order By: Relevance
“…As one of the most important components of the ECM 31 , Col is undoubtedly the most frequently used natural protein in the nervous system 32,33 , and is widely used as a biological scaffold for nerve regeneration [34][35][36] . It is shown that Col could help nerve regeneration with/without growth factors [37][38][39][40][41][42] .…”
Section: Extracellular Matrixmentioning
confidence: 99%
“…As one of the most important components of the ECM 31 , Col is undoubtedly the most frequently used natural protein in the nervous system 32,33 , and is widely used as a biological scaffold for nerve regeneration [34][35][36] . It is shown that Col could help nerve regeneration with/without growth factors [37][38][39][40][41][42] .…”
Section: Extracellular Matrixmentioning
confidence: 99%
“…Cross-linking strategies have been developed in an effort to improve their mechanical strength and stability. Collagen has been a popular choice, as it is readily available, has low immunological properties, good biocompatibility, a porous structure, and is biodegradable [12].…”
Section: Nerve Guide Conduitsmentioning
confidence: 99%
“…Growth factor analogs, such as bFGF and VEGF, play crucial roles in wound healing, tissue regeneration, angiogenesis, and nerve regeneration. [407][408][409] As previously mentioned, the short half-life and rapid diffusion of exogenous growth factors in body fluids result in decreased utilization efficiency, often necessitating high doses or repeated applications to achieve therapeutic effects. 410,411 Capitalizing on the benefits of collagen, we have employed it to encapsulate growth factors and facilitate targeted transport to wound areas, thereby enhancing the woundhealing process, which is closely tied to vascular and nerve regeneration.…”
Section: Collagen Scaffolds Loaded With Therapeutic Factormentioning
confidence: 99%
“…Growth factor analogs, such as bFGF and VEGF, play crucial roles in wound healing, tissue regeneration, angiogenesis, and nerve regeneration 407–409 . As previously mentioned, the short half‐life and rapid diffusion of exogenous growth factors in body fluids result in decreased utilization efficiency, often necessitating high doses or repeated applications to achieve therapeutic effects 410,411 .…”
Section: The Future Of Regenerative Medicine In Cyclical Endometrial ...mentioning
confidence: 99%